2010
DOI: 10.1007/s00432-010-0900-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum TNF-α, B2M and sIL-2R levels are biological correlates of outcome in adjuvant IFN-α2b treatment of patients with melanoma

Abstract: Low TNF-α levels are negatively associated with relapse-free survival. Conversely, high TNF-α levels are correlated with toxicity but seem to be beneficial to patients with regard to relapse-free survival. B2M and sIL-2R are biological markers of adjuvant IFN-α2b treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…5 Experimental studies indicate that TNF plays an important role in the growth regulation of melanomas, 13 and recent clinical data link relapse of melanoma with low concentrations of TNF. 14 Isolated limb perfusion with TNF is a therapeutic approach used in advanced melanoma, supporting the notion of TNF as a protective cytokine in certain clinical manifestations of melanoma. 15 16 As supported by a recent review, most, [17][18][19] but not all, 6 11 observational studies report no increased risk of melanoma in patients with rheumatoid arthritis not treated with biological drugs compared with the general population (supplementary table A).…”
Section: Introductionmentioning
confidence: 93%
“…5 Experimental studies indicate that TNF plays an important role in the growth regulation of melanomas, 13 and recent clinical data link relapse of melanoma with low concentrations of TNF. 14 Isolated limb perfusion with TNF is a therapeutic approach used in advanced melanoma, supporting the notion of TNF as a protective cytokine in certain clinical manifestations of melanoma. 15 16 As supported by a recent review, most, [17][18][19] but not all, 6 11 observational studies report no increased risk of melanoma in patients with rheumatoid arthritis not treated with biological drugs compared with the general population (supplementary table A).…”
Section: Introductionmentioning
confidence: 93%
“…In terms of relapse-free survival, increased serum levels of TNF-alpha seem to have a protective role before and -despite high toxicityafter treatment 87 . The prognostic value of TNFalpha is still a subject of debate, since past studies have shown no relevant correlation between plasma levels of TNF-alpha and clinical outcome of patients with primary melanoma and negative sentinel lymph node 88 .…”
Section: Circulatory Inflammatory Markersmentioning
confidence: 99%
“…Patients homozygous for rs10964859 (HR = 2.01, 95% CI 1.17, 3.44; p = 0.01) and rs10964862 (HR 1.84, 95%CI 1.03, 3.27, p = 0.04) were associated to increased risk of death following metastasis Gogas et al [83] HLA gene The median relapse-free survival of the Cw 06-positive cohort was 100.2 months versus 37.3 months in the Cw 06-negative cohort (p = 0.013) Hofmann et al [86] Serum cytokines At baseline, the combination of TNF-a, B2 M and sIL-2R revealed a positive predictive value for relapse of 82.9% in the multivariate analyses lost, thereby demonstrating the lack of usefulness of serum autoantibodies as a prognostic factor [84].…”
Section: Referencementioning
confidence: 94%
“…Interestingly, baseline levels of TNF-a levels were correlated with increased toxicity, but also with a longer RFS. Furthermore, the combined assessment of TNF-a, B2M and sIL-2R showed a positive predictive value for relapse of 82.9% in the multivariate analyses, which indicates that these biomarkers can be useful in identifying patients who could benefit from adjuvant treatment [86]. Another interesting approach is to measure early changes in IFN signaling capacity in peripheral blood lymphocytes of patients treated with IFN.…”
Section: Referencementioning
confidence: 95%